HIV/AIDS knowledge, awareness and perception of undergraduate first-year students at the Cape Institute for Agricultural Training : higher education and training - Huisamer, Zelda Patricia (Stellenbosch : University of Stellenbosch, 2010)
Thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy (HIV/AIDS Management) at the Stellenbosch University